2016
DOI: 10.1152/jn.00918.2015
|View full text |Cite
|
Sign up to set email alerts
|

Efficient neuroplasticity induction in chronic stroke patients by an associative brain-computer interface

Abstract: Mrachacz-Kersting N, Jiang N, Stevenson AJ, Niazi IK, Kostic V, Pavlovic A, Radovanovic S, Djuric-Jovicic M, Agosta F, Dremstrup K, Farina D. Efficient neuroplasticity induction in chronic stroke patients by an associative brain-computer interface. J Neurophysiol 115: 1410 -1421, 2016. First published December 30, 2015 doi:10.1152/jn.00918.2015 have the potential to improve functionality in chronic stoke patients when applied over a large number of sessions. Here we evaluated the effect and the underlying mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
264
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 205 publications
(284 citation statements)
references
References 71 publications
7
264
1
4
Order By: Relevance
“…showed improved ipsilesional connectivity in the mu and beta bands after BCI‐NMES training compared to a group undergoing placebo‐BCI training. Other studies have reported shifts in hemispheric EEG activity41 and increase in ipsilesional movement‐related cortical potentials as well as motor‐evoked potentials 56. In addition, some of these neurophysiological measures correlated with behavioral improvements: (1) EEG‐based Brain Symmetry index could predict the functional motor outcomes in Ang et al.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…showed improved ipsilesional connectivity in the mu and beta bands after BCI‐NMES training compared to a group undergoing placebo‐BCI training. Other studies have reported shifts in hemispheric EEG activity41 and increase in ipsilesional movement‐related cortical potentials as well as motor‐evoked potentials 56. In addition, some of these neurophysiological measures correlated with behavioral improvements: (1) EEG‐based Brain Symmetry index could predict the functional motor outcomes in Ang et al.…”
Section: Discussionmentioning
confidence: 91%
“…We also identified three studies that targeted lower limb: (1) Mrachacz‐Kersting et al 56. reported improvements in FMA for lower extremity score (mean difference of 0.8 ± 0.46) in chronic stroke patients ( N  = 22), where they estimated reaction time from offline EEG, which was then used for delivering peroneal nerve stimulation during interventional trials (i.e., online trials), but not in the sham feedback group.…”
Section: Resultsmentioning
confidence: 99%
“…The MRCP is a slow cortical potential that has been associated with voluntarily executed, self-paced or imagined movements (Hallett, 1994). By pairing the intent of the participant with the artificial production of the imagined or intended movement, we have shown significant plastic changes within the motor cortex of both healthy participants and patients (Scheel et al, 2015;Mrachacz-Kersting et al, 2015). Patients also significantly increased their 10 m walking speed and foot tapping frequency.…”
Section: Introductionmentioning
confidence: 90%
“…In a study by Mrachacz-Kersting et al (2016) only patients receiving a single pulse stimulus precisely matched with the maximum negativity of MRCP improved their speed of walking. Interestingly, although patients practiced isolated ballistic foot dorsiflexion it translated to the improvement of walking.…”
Section: Discussionmentioning
confidence: 98%